Dynamics of Photothermally Created Vaporous, Gaseous, and Mixed Microbubbles - Dharmadhikari, Aditya K; Dharmadhikari, Jayashree A; Mahulkar, Amit V; Ramanandan, Gopika; Ramachandran, Hema; Pandit, Aniruddha B; Mathur, Deepak (Journal of physical chemistry. C, 2011)
Carbon nanotubes suspended in various liquids act as absorbers of low-power (mW), continuous-wave laser (1064 nm) light and cause photothermal generation of microbubbles. Three types of microbubbles, gaseous, vaporous, and mixed, are experimentally and theoretically characterized, allowing diverse applications to be identified where one or the other kind may be better suited. Bubbles collapse after reaching a certain size. Imploding cavitational collapse of vaporous bubbles produces exploding shockwaves while nonspherical collapse generates high-speed liquid jets, resulting in spectacular disruption of proximate matter; localized temperatures in excess of 4000 K are predicted. Small fractions of noncondensable gases in vaporous bubbles are found to significantly alter the dynamics.